Patient and Patient's Relatives Participation Strategy in the Prevention of Infections: Hand Hygiene - Meltem Dursun Engin; Şeyda Seren İntepeler (Association of Nurse Managers, 2022)
Medical errors are inevitable because health services are provided by more than one professional group and the institutions served have complex structures. The most important priority in providing healthcare services is not to harm the patient. In this regard, ensuring patient safety emerges as the main priority. It is extremely important to include patients and their relatives in patient safety practices, keeping in mind that they are a part of the team. The contribution of patients and their relatives to safety measures, especially within the scope of preventing infections, is emphasized in the literature. In the strategies to be practiced, it is recommended to prioritize hand hygiene, a simple and cost-effective way of preventing infections, with the participation of patients and their relatives to ensure empowerment. In line with the literature, this review aims to discuss hand hygiene practices, one of the important issues in patient safety, with the patient and patient relatives' participation in strategies preventing infections.